The Factors Related to The Happiness among Sexual-and Gender-Diverse Persons - Prakobchai, Sattaya; Soonthornchaiya, Rangsiman; Imkome, Ek-uma (Journal of The Royal Thai Army Nurses, 2021)
This descriptive correlational researchwas examined the following: 1) the happiness among sexually- and gender-diverse individuals (SGD), and 2) the factors influencing the happiness of these individuals. One hundred and fifty-two sexually- and gender-diverse individuals were recruited. The instruments included the following: 1) a demographic characteristics questionnaire; 2) a family relationship questionnaire; 3) the Rosenberg Self-esteem Scale;4) the Center of Epidemiologic Studies Depression Scale (CSD-S), and 5) the Oxford Happiness Questionnaire. Cronbach’s alpha was used to determine the reliability of the instruments. Family relationship Questionnaire was at .75, Rosenberg Self-esteem scale was at.71, CES-D was at .80, and the Oxford Happiness Questionnaire was at .75. Data were analyzed using descriptive statistics and Spearman’s correlation coefficient. The results revealed that the happiness was at a high level (M = 4.67, SD. = .59), family relationships were at a good level (M = 48.63, SD. = 7.17), self-esteem was at a high level (M = 3.30, SD. = .44), and depression was at 10.80 (SD. = 8.59). Family relationships and self-esteem had a statistically-significant positive relationship with happiness (r = .38, p<0.001, r = .66, p<.001), and depression had a statistically significant negative relationship with happiness (r = -.60, p<.001) Although happiness among SGD was at a high level, mental health nurses should develop nursing interventions by promoting family relationships and self-esteem. Moreover, depression is negatively correlated with happiness. Mental health nurses could early detect, prevent, and follow-up for depression among sexually-and gender-diverse persons.